2017
DOI: 10.1186/s13046-017-0618-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of DARS2 by HBV promotes hepatocarcinogenesis through the miR-30e-5p/MAPK/NFAT5 pathway

Abstract: BackgroundInfection with the hepatitis B virus (HBV) is closely associated with the development of hepatocellular carcinoma (HCC). The osmoregulatory transcription factor nuclear factor of activated T-cells 5 (NFAT5) has been shown to play an important role in the development of many types of human cancers. The role of NFAT5 in HBV-associated HCC has never previously been investigated.MethodsWe compared expression profiles of NFAT5, DARS2 and miR-30e-5p in HCC samples, adjacent nontumor tissues and different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 44 publications
(40 reference statements)
1
56
0
Order By: Relevance
“…Based on review of the literature (present study), miR‐30e‐5p modulates diverse mRNA targets in different disease situations, including cancer. These target genes are listed as follows: NFAT5 , TUSC3 , Bim , USP22 , MYBL2 , ITGA6 , ITGB1 , LRP6 and YAP1 . In our current study, miR‐30e‐5p was found to directly link to the 3′‐UTR domain of AEG‐1 mRNA, which accelerates the degradation of AEG‐1 mRNA and eventually reduces the level of AEG‐1 protein.…”
Section: Discussionsupporting
confidence: 49%
“…Based on review of the literature (present study), miR‐30e‐5p modulates diverse mRNA targets in different disease situations, including cancer. These target genes are listed as follows: NFAT5 , TUSC3 , Bim , USP22 , MYBL2 , ITGA6 , ITGB1 , LRP6 and YAP1 . In our current study, miR‐30e‐5p was found to directly link to the 3′‐UTR domain of AEG‐1 mRNA, which accelerates the degradation of AEG‐1 mRNA and eventually reduces the level of AEG‐1 protein.…”
Section: Discussionsupporting
confidence: 49%
“…CTU1 copy number ampli cations were identi ed in 25% of myxopapillary ependymomas [39]. Qin et al had demonstrated DARS2 as a hepatocarcinoma gene that could promote the progression of hepatocarcinoma cell cycle and inhibit the apoptosis of hepatocarcinoma cells [40]. EFTUD2 gene expression was upregulated in hepatocarcinoma, and had prognostic signi cance in patients with hepatocarcinoma [41].…”
Section: Discussionmentioning
confidence: 99%
“…CDK5, c-Abl, and ATM promote the nuclear localization of NFAT5, and, in contrast, CK1 inhibits its nuclear accumulation [19]. There are many other factors that influence the activation and expression of NFAT5, such as inflammatory cytokines [16, 77], microRNAs [50, 62, 78, 79], and transcription factors [80-83]. …”
Section: The Regulation Of Nfat5 Activationmentioning
confidence: 99%